Do We Use FLOSS in Software Engineering Education? Mapping the Profiles and Practices of Higher Education Teachers from Brazil - Silva, Fernanda Gomes; Santos, Paulo Ezequiel Dias dos; Chavez, Christina von Flach G. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Context: Software Engineering (SE) is a key topic in undergraduate computing-related courses that provides the basic knowledge and skills necessary for professional practice in the software industry. Teaching SE principles, concepts and practices and relating them to real-world scenarios are challenging tasks, and the adoption of Free/Libre/Open Source Software (FLOSS) projects can help to face these challenges. On the other hand, using FLOSS projects as a didactic resource may introduce additional challenges to professors that are not familiar with the FLOSS ecosystem. Objective: This research aims to identify and map the profiles of professors of SE courses in Brazil, as well as to present the pedagogical practices used in the experience with FLOSS projects in Software Engineering Education (SEE). Method: We performed a survey with higher education professors in Brazil, used K-modes algorithm to identify clusters and Decision Tree algorithm to identify characteristics that determine the use of FLOSS projects in a sample of professors who had not used this approach in the classroom. Results: The results of the research revealed characteristics of professors who use, or not, FLOSS projects in SEE, of professors grouped in the two clusters generated by the application of the K-modes algorithm, of professors grouped by the application of the Decision Tree algorithm, in addition to presenting similar characteristics the pedagogical practices evidenced by each group of SE professors.